Relative benefits of linear analogue and advanced digital hearing aids. - Wood SA; Lutman ME (International Journal of Audiology, 2004)
Speech recognition performance and self-reported benefit from linear analogue and advanced (digital) hearing aids were compared in 100 first-time hearing aid users with mild-to-moderate sensorineural hearing loss fitted monaurally with a behind-the-ear (BTE) hearing aid in a single-blind randomized crossover trial. Subjects used each aid for 5 weeks in turn, with aid order balanced across subjects. Three alternative models of digital hearing aid were assigned to subjects according to a balanced design. Aid type was disguised to keep subjects blind within practical limitations. Aided speech recognition performance in noise was measured at speech levels of 65 and 75dB at a speech-to-noise ratio (SNR) of +2dB for closed sets of single words. Self-rated benefit was measured using the Abbreviated Profile of Hearing Aid Benefit (APHAB) and the Glasgow Hearing Aid Benefit Profile (GHABP). Quality of life, hearing aid use and user preferences were also assessed. Speech recognition scores with the digital aids were significantly better at 75dB than with the analogue aids Self-reported benefit (APHAB, GHABP) and improvement in quality of life were generally not significantly different between analogue and digital aids, although aversiveness measured with the APHAB was significantly lower with digital aids, and satisfaction measured with the GHABP was greater. The digital aids were preferred significantly more often than the analogue aids, with 61 subjects choosing their digital aid, 26 choosing the analogue aid, and nine being equivocal. Overall, this study shows advantages for advanced digital over simple linear analogue aids in terms of both objective and subjective outcomes, although average differences are not large.